Gestational and congenital syphilis in a municipality in Brazil between 2014 and 2018 - Silva, Patricia Simon da; Vieira, Cassandra Severo Amaral; Gomes, Ludmila Mourão Xavier; Barbosa, Thiago Luis de Andrade (Brazilian Journal of Sexually Transmitted Diseases, 2019)
Introduction: Syphilis is an infectious disease that can cause congenital syphilis when it affects pregnant women, resulting in malformation of the fetus, miscarriage, or fetal death. Unlike many neonatal infections, congenital syphilis is considered a preventable perinatal cause, because it can be diagnosed and treated early during pregnancy. Objective: To analyze the reports of cases of gestational syphilis and congenital syphilis registered in Foz do Iguaçu City, Paraná State, between 2014 and 2018. Methods: This is a time-series study on the trend of cases recorded in the Notification Diseases Information System. The simple linear regression model was adopted to verify the trend of deaths in the analyzed period. Results: A total of 324 reports of gestational syphilis and 137 cases of congenital syphilis were evidenced in the study period. Regarding cases of gestational syphilis, 45.9% were diagnosed during the first trimester of pregnancy, 74.6% were treated with penicillin, and 24.3% were classified as primary syphilis. Roughly 88.3% of cases of congenital syphilis were reported in children under the age of 7 days. A significant increase in the rate of detection of gestational syphilis was observed, representing an increase of 4.0 times (p=0.004) in the years analyzed, and the risk of congenital syphilis increased 5.8 times (p=0.003) in the same period. Conclusion: The magnitude of gestational and congenital syphilis is a warning that indicates the need for actions and strategies to reduce cases of gestational syphilis and vertical transmission of syphilis.